Distribution of Sensitizer-Induced Occupational Asthma - Jordan Minov; Jovanka Karadzinska-Bislimovska; Kristin Vasilevska; Snezana Risteska-Kuc; Saso Stoleski; D. Mijakoski (Global Journal of Allergy - Peertechz Publications, 2015)
Introduction: Occupational asthma (OA) became an important public health problem worldwide in the last few decades. From two different OA types, sensitizer-induced OA accounts for approximately 90% of all OA cases. Aim of the study was to present the distribution of sensitizer-induced OA by occupation in R. Macedonia in the period 2005-2014. Methods: Sensitizer-induced OA was diagnosed by serial measurement of peak expiratory flow (PEF) at and away from work or by combination of serial PEF measurement at and away from work and non-specific bronchial provocation at and away from work in subjects with diagnosed asthma and work-relatedness of the symptoms. Results: The annual incidence rate of the diagnosed sensitizer-induced OA in the mentioned period varied from 1.8/100,000 working population in 2013 to 2.8/100,000 in 2006. Sensitizer-induced OA in bakers, cleaners, textile workers and agricultural workers accounted up to more than a third of the all diagnosed cases. Atopy was registered in approximately a half of the sensitized-induced OA cases. Majority of the cases with sensitizer-induced OA caused by HMW agents (i.e. OA in bakers, textile workers, tanners, herbal and fruit tea processors, and health care workers) was atopics and had positive prick tests to occupational allergens. Conclusion: Our findings indicate the sectors with highest occurrence of sensitizer-induced OA in R. Macedonia in the period 2005-2014. The data obtained enable directing of adequate activities to prevent developing of the disease, as well as to identify affected ones and to prevent further respiratory impairment.